Metformin ameliorates polycystic ovary syndrome in a rat model by decreasing excessive autophagy in ovarian granulosa cells via the PI3K/AKT/mTOR pathway - Xu, Bo; Dai, Wenjie; Liu, Ling; Han, Hang; Zhang, Jingjing; Du, Xing; Pei, Xiuying; Fu, Xufeng (Endocrine Journal, 2022)
Polycystic ovary syndrome (PCOS) is a common gynecological disease accompanied by a variety of clinical features, including anovulation, hyperandrogenism, and ovarian abnormalities, resulting in infertility. PCOS affects approximately 6%–15% of all reproductive-age women worldwide. Metformin, a popular drug used to treat PCOS in patients, has beneficial effects in reducing hyperandrogenism and inducing ovulation; however, the mechanisms by which metformin ameliorates PCOS are not clear. Hence, we aimed to explore the mechanisms of metformin in treating PCOS. In the present study, we first treated a letrozole-induced PCOS rat model with metformin, detected the pathological recovery of PCOS, and then assessed the effects of metformin on H2O2-induced autophagy in ovarian granulosa cells (GCs) by detecting the level of oxidative stress and the expression of autophagy-associated proteins and key proteins in the PI3K/AKT/mTOR pathway. We demonstrated that metformin ameliorated PCOS in a rat model by downregulating autophagy in GCs, and metformin decreased the levels of oxidative stress and autophagy in H2O2-induced GCs and affected the PI3K/AKT/mTOR signaling pathway. Taken together, our results indicate that metformin ameliorates PCOS in a rat model by decreasing excessive autophagy in GCs via the PI3K/AKT/mTOR pathway, and this study provides evidence for targeted reduction of excessive autophagy of ovarian granulosa cells and improvement of PCOS.